MENEMBUS PASAR GLOBAL: PERFORMA DAN DAMPAK KETERBUKAAN PERDAGANGAN TERHADAP EKSPOR MANUFAKTUR INDONESIA - hotsawadi, hotsawadi; Gea, Imelda Veronica (LPPM - STIE SAKTI ALAM KERINCI, 2025)
The Indonesian manufacturing sector still faces various problems in the global market consisting of increasingly high product competition and relatively low added value. Therefore, this study aims to identify the competitiveness and influence of the level of trade openness on the performance of Indonesian manufacturing exports using the method of analyzing the degree of trade openness, Revealed Comparative Advantage (RCA) which is enhanced by the Revealed Symmetric Comparative Advantage (RSCA) method, Trade Balance Index (TBI) and panel data regression. The results of the analysis found that the structure of Indonesian manufacturing exports tends to focus on low or medium technology products, while high-tech products that have greater added value are still dominated by imports. Viewed from the side of the degree of openness, it was found that the average degree of trade openness was lower than other ASEAN countries such as Singapore, Malaysia, and Vietnam. Low trade openness has the potential to open up global market access which ultimately limits Indonesia's opportunities to expand its market share. Meanwhile, the analysis of the results of panel data regression shows that the variables of the degree of trade openness, GDP per capita of each trading partner country, Indonesia's GDP per capita, the real exchange rate and competitiveness have a positive and significant effect on the export performance of the Indonesian manufacturing sector. Meanwhile, the population of partner countries has a negative and significant effect on Indonesia's manufacturing sector exports.